Spatio-temporal patterns of lumpy skin disease outbreaks in dairy farms in northeastern Thailand - Punyapornwithaya, Veerasak; Seesupa, Suvaluk; Phuykhamsingha, Sitthinon; Arjkumpa, Orapun; Sansamur, Chalutwan; Jarassaeng, Chaiwat (Frontiers in Veterinary Science, 2022)
In 2021-2022, there were numerous outbreaks of lumpy skin disease (LSD) affecting cattle farms across Thailand. This circumstance was the country's first experience with an LSD outbreak. Thus, it is critical to gain a better understanding of LSD and its impact on dairy production. The aims of this study were i) to determine the spatio-temporal outbreak patterns and ii) to assess the impact of the LSD outbreak on farm milk production. Outbreak investigation and milk production data from dairy farms located in northeastern Thailand were analyzed using spatio-temporal modelling approaches and generalized linear mixed models to determine clusters of disease and to compare the differences in milk production, respectively. LSD outbreaks were found in 133 farms, and the overall morbidity and mortality rates were 31% and 0.9%, respectively. The space-time permutation and Poisson model identified 15 and 6 spatiotemporal outbreak clusters, respectively, while the Bernoulli model provided only one cluster. The most likely clusters from those models cover radii of 1.59, 4.51 and 4.44 km, respectively. Overall, monthly farm-level milk production continuously decreased by more than 8% from May to August 2021. The average milk drop was 7.1 liters per farm per day during this period. Considering milk production from June to July in 2020 and 2021, the total milk production of LSD-affected farms in the outbreak year was statistically lower than that in the previous year. Furthermore, it is estimated that 2,413,000 Thai Baht (6,9724 USD) has been lost as a result of this outbreak due to milk production losses. On average, farmers lost 4,047 baht (117 USD) per month from May to August. The results from the present study provide better insight into the spatiotemporal pattern of clusters of LSD in the outbreak area. In addition, this study first demonstrated that LSD outbreaks in dairy farms in Thailand resulted in significant milk production losses. The findings of this study can support authorities in formulating strategies to prevent and control future outbreaks as well as comprehending the negative impact of LSD on milk production.